Modern Money - L. Randall Wray (Levy Economics Institute of Bard College, 1998)
All modern economies have a "chartalist" or "state" money, as acknowledged by Friedrich Knapp and J. M. Keynes. In this paper, I examine the "history" of money to shed light on its origins. I also examine in detail the views of those who accepted the chartalist, or state, approach to money, from Adam Smith to Knapp and Keynes, with some discussion of the views of Hyman Minsky and Abba Lerner. This is then linked to Lerner's "functional finance" approach to money and government spending. I next explore the implications of "modern money" for government policy and show that much economic analysis reaches erroneous conclusions because it fails to recognize the nature of modern money. The state "defines" money when it chooses that in which taxes must be paid. Government spending is the most important determinant of the supply of base money; government deficits are the most important source of net money holdings. This stands in stark contrast to traditional analysis, for fiscal policy is the primary determinant of the money supply and monetary policy determines the short-term interest rate. Because government deficits increase bank reserves, monetary policy is required to offer an interest-earning alternative to excess reserves; essentially, monetary policy consists of sales of government bonds (by the Treasury and central bank) to "drain" excess reserves in order to hit the interest rate target established for monetary policy. Thus, bond sales are not a part of fiscal policy nor are they needed to "finance" government deficits. This analysis leads to several interesting policy conclusions regarding the importance of government deficits and debts and regarding proposals to promote full employment.
Keywords: 330